KUALITAS LAYANAN PADA FRONTLINER DI PERGURUAN TINGGI SWASTA SURABAYA - Selviana Novela Suryadiningsih; Andhika Alexander Repi (EXPERIENTIA : Jurnal Psikologi Indonesia, 2019)
Optimal service quality is related to customer satisfaction which can have an impact on organization's existence. All industrial sectors such as educational institutions, including PTS X, need to optimize their service quality. Results of preliminary research showed that students as the frontliner users of PTS X General Administration Bureau evaluated the bureau as having less-than-optimal quality of service. This study aimed to examine and describe the quality of service of the PTS X General Administration Bureau. Participants were PTS X students who were recruited using incidental sampling technique. The scale of service quality, comprising different aspects such as tangible appearance, reliability, responsiveness, assurance, and empathy, was used as a method of data collection, meanwhile descriptive analysis was used as data analysis technique. Result showed that the quality of service of PTS X General Administration Bureau was perceived at a high level, meaning that students as the service users provided a good evaluation to the service. This was different from the result of preliminary study. Different findings may be due to the implementation of new information technology system as well as self-improvement efforts made continuously by PTS X. Despite this, the head of PTS X General Administration Bureau still needs to optimize human resources within the organization, including the frontliner staff. The management of PTS X should develop the quality of service not only within the General Administration Bureau, but also in other bureau and departements of PTS X.